2020
DOI: 10.3892/etm.2020.9076
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of three cryoprotectants on the cryopreservation of mouse subcutaneous tissue under different conditions

Abstract: The subcutaneous tissue of animals contains different cell types, and different cells have different requirements for cryopreservation. This establishes obstacles that need to be overcome in the clinical application of tissue preservation. In the present study, the effects of different freezing rates and various concentrations of cryoprotectants on the cryopreservation of subcutaneous tissue of mice were compared, and these results provided basic research data that can be used to explore the optimal cryopreser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…For instance, Naaldijk et al compared the effects of different machine-based and manual cryopreservation methods on the post-thaw survival and proliferative capacity of human fibroblasts, and suggested that the freezing-container method was the most effective solution [ 4 ]. Wang et al revealed that mouse ( Mus musculus ) fibroblasts’ post-thaw recovery rate under slow cryopreservation was significantly higher than that under rapid freezing [ 16 ]. Costa et al indicated that both direct vitrification in cryovials and solid-surface vitrification were effective in the preservation of agouti ( Dasyprocta leporina Linnaeus ) fibroblasts, but led to an increase in the number of perinuclear halos [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Naaldijk et al compared the effects of different machine-based and manual cryopreservation methods on the post-thaw survival and proliferative capacity of human fibroblasts, and suggested that the freezing-container method was the most effective solution [ 4 ]. Wang et al revealed that mouse ( Mus musculus ) fibroblasts’ post-thaw recovery rate under slow cryopreservation was significantly higher than that under rapid freezing [ 16 ]. Costa et al indicated that both direct vitrification in cryovials and solid-surface vitrification were effective in the preservation of agouti ( Dasyprocta leporina Linnaeus ) fibroblasts, but led to an increase in the number of perinuclear halos [ 17 ].…”
Section: Introductionmentioning
confidence: 99%